Mota : modern taxiing using robot motion planning theory - Yang, Jingyi (2016)
In this report, algorithms are designed and implemented for airport traffic flow management. The algorithms are modified and improved based on the state-of-art of robot motion planning theory--the Rapidly-exploring Random Tree (RRT) algorithm. Firstly, a physical path for each aircraft is planned individually. After that, velocity of each aircraft is planned in coordination diagram by a Virtual-Box RRT algorithm. The algorithm is featured to allow aircraft arriving at their corresponding destinations at di fferent timings, giving priority to airplanes with shorter physical paths. If one airplane has reached its destination, dimensions are reduced and therefore, the computational complexity is reduced. By applying Virtual-Box RRT, the computational time for velocity pro file of 10 airplanes is limited to 3 seconds. In addition, the deadlock problem raised by dimension reduction is solved by creating a "virtual obstacle" in coordination diagram. To reduce computational and spacial complexity, the "virtual obstacle" is not created explicitly. Instead, every new confi guration that will be connected to the RRT is restricted from falling in the deadlock region. As a real-time continuous planner, new departures and arrivals of aircraft are simulated. It also demonstrates path and velocity coordination for more than 1 aircraft with the same destination. With strictly prohibited backwards motion, this planner guarantees to resolve the deadlock issue if there is one.